2022
DOI: 10.3847/1538-4357/ac77fd
|View full text |Cite
|
Sign up to set email alerts
|

The ALMaQUEST Survey. VIII. What Causes the Discrepancy in the Velocity between the CO and Hα Rotation Curves in Galaxies?

Abstract: We compare the CO(1–0) and Hα kinematics in 34 nearby galaxies, selected from the ALMaQUEST and EDGE-CALIFA surveys. We use 3D-Barolo, a 3D tilted-ring model, to derive the CO and Hα rotation curves. Before comparing rotation curves in the 34 nearby galaxies, we found systematics between the MaNGA and CALIFA data using eight MaNGA-CALIFA overlapping galaxies. We assume the rotation curves based on the MaNGA data are accurate and made the corresponding correction to the CALIFA data. Our result shows that ∼56% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…We note that only 7/41 galaxies from the Genzel et al (2020) sample are observed in molecular gas, with the remainder being ionized gas, and Übler et al (2021) also model this gas phase. However, several published studies find very little measurable difference in rotation curves derived from ionized versus molecular gas (Genzel et al 2013;Übler et al 2018;Su et al 2022). 12/14 of the galaxies in our sample have higher asymmetry than the average galaxy in the Genzel et al (2020) sample, and 7/14 have higher asymmetry than the average galaxy in the Übler et al (2021) sample.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…We note that only 7/41 galaxies from the Genzel et al (2020) sample are observed in molecular gas, with the remainder being ionized gas, and Übler et al (2021) also model this gas phase. However, several published studies find very little measurable difference in rotation curves derived from ionized versus molecular gas (Genzel et al 2013;Übler et al 2018;Su et al 2022). 12/14 of the galaxies in our sample have higher asymmetry than the average galaxy in the Genzel et al (2020) sample, and 7/14 have higher asymmetry than the average galaxy in the Übler et al (2021) sample.…”
Section: Discussioncontrasting
confidence: 49%
“…Furthermore, inspection of the CO-Hα velocity curves for each galaxy in the ALMaQUEST subsample does not show significant asymmetric differences as a function of distance from the galaxy center. While it is unknown how much the difference in CO-Hα velocity curves may vary over cosmic time or with environment, a difference like that from the Su et al (2022) sample is insignificant compared to the other sources of uncertainty we already take into account. Furthermore, certain environmental effects that are particularly strong in dense environments, like ram pressure, are expected to have an even greater impact on the kinematics of the less dense ionized phase than the denser molecular gas, as has been observed, for example, in Boselli et al (1994).…”
Section: Girard Et Al 2021mentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, we have an almost perfect agreement between the kinematic of the stars and that of the interstellar medium. This is not always the case, because in several galaxies, these two components have different rotational patterns (see, e.g., Williams et al 2021;Su et al 2022).…”
Section: Kinematics Of Stars and Gasmentioning
confidence: 99%